Legal Review in Handling FBI Fugitives who Fled to Indonesia: Russ Medlin Case Study - Alief Heidar Sardjono; Fikri Rahmat Fadila; Kevin Figo Saragih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Law enforcement can be done by cooperation between agencies both nationally and internationally. One case that requires international cooperation in the disclosure of crimes is the case of Russ Medlin who is an FBI fugitive who fled to Indonesia for shelter. Russ Medlin not only committed his crimes in his home country but also in Indonesia. International and national law enforcement authorities are working together to arrest him in Indonesia. The research method used is a normative approach. The result of this study is the cooperation of international and national law enforcement authorities such as the International Police, FBI, POLRI, Indonesian immigration to arrest Russ Medlin despite the obstacles in the form of delays in sending red notices to Indonesian immigration authorities. In order not to happen again, in the future in sending red notices must be issued immediately so that they can be prevented before entering Indonesia so as not to cause new cases.